Transaksi Jual Beli dan Fiqih Media Sosial - Nur Annisa Tri Handayani; Ahmadih Rojalih Jawab (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
In the modern digital era, the phenomenon of buying and selling via social media has experienced rapid development. Transactions using online media from the point of view of buying and selling jurisprudence are permitted in Islam in accordance with the jurisprudence rules "Al-Ashl fi mu’amalah al-ibhah, illa idza ma dalla al-dalil ala khilafihi" as long as in the process no elements occur. which are contrary to Islamic law, such as fraud, ambiguity and usury. This research aims to analyze buying and selling transactions via social media from the perspective of Islamic jurisprudence and the related ethical implications. The purpose of this writing is to explore the issues that arise along with the increase in buying and selling transactions on social media platforms and identify how fiqh principles can guide ethical behavior in the context of buying and selling. The results of the research are that there are two forms of contract that can be adopted in contemporary online transactions, the bay’ al murabahah contract, namely the sale and purchase of goods at the original price with additional agreed profits and the bay’ as-salam contract, namely the provision of goods that are handed over at a later date while payment is made at an early date. transaction is carried out.